Enhancing Maritime Education: Qualitative Analysis of Training Methodologies in Transportation and Logistics - Rosmayana, Rosmayana (Jurnal Pendidikan Indonesia : Teori, Penelitian, dan Inovasi, 2025)
This study examines the effectiveness of maritime education methodologies in preparing cadets for careers in transportation management, logistics, port operations, and transportation safety. Using a qualitative research approach with descriptive analysis, the study evaluates 100 cadets across multiple maritime institutions adhering to international standards. Key findings indicate that while curricula align with IMO and STCW frameworks, challenges exist in technological integration, pedagogical engagement, and research methodology application. The study highlights the necessity of shifting assessment strategies from traditional theoretical evaluations to competency-based and scenario-driven approaches. Additionally, digital learning tools, artificial intelligence, and big data are underutilized in maritime education, limiting cadet preparedness for modern industry demands. The research also identifies gaps in transportation literacy and interdisciplinary logistics training. Recommendations include curriculum modernization, enhanced digital infrastructure, research-driven pedagogy, and stronger industry partnerships to ensure cadets develop the skills required in an evolving transportation landscape. These improvements will enable maritime institutions to bridge the gap between theoretical knowledge and industry-ready competencies, fostering a more adaptive and proficient workforce.ABSTRAKStudi ini mengkaji efektivitas metodologi pendidikan maritim dalam mempersiapkan taruna untuk berkarir di bidang manajemen transportasi, logistik, operasi pelabuhan, dan keselamatan transportasi. Dengan menggunakan pendekatan penelitian kualitatif dengan analisis deskriptif, studi ini mengevaluasi 100 taruna di berbagai institusi maritim yang mengikuti standar internasional. Temuan utama menunjukkan bahwa meskipun kurikulum selaras dengan kerangka kerja IMO dan STCW, terdapat tantangan dalam integrasi teknologi, keterlibatan pedagogis, dan aplikasi metodologi penelitian. Studi ini menyoroti perlunya pergeseran strategi penilaian dari evaluasi teoretis tradisional ke pendekatan berbasis kompetensi dan skenario. Selain itu, alat pembelajaran digital, kecerdasan buatan, dan data besar kurang dimanfaatkan dalam pendidikan maritim, sehingga membatasi kesiapan taruna untuk menghadapi tuntutan industri modern. Penelitian ini juga mengidentifikasi kesenjangan dalam literasi transportasi dan pelatihan logistik interdisipliner. Rekomendasi yang diberikan mencakup modernisasi kurikulum, peningkatan infrastruktur digital, pedagogi berbasis penelitian, dan kemitraan industri yang lebih kuat untuk memastikan para taruna mengembangkan keterampilan yang dibutuhkan dalam lanskap transportasi yang terus berkembang. Peningkatan ini akan memungkinkan institusi maritim untuk menjembatani kesenjangan antara pengetahuan teoretis dan kompetensi yang siap pakai di industri, sehingga mendorong tenaga kerja yang lebih adaptif dan mahir.